Interaction of psoriasis and pregnancy: Maternal and fetal outcomes - Sevgi Akarsu (Archives of Anatomy and Physiology - Peertechz Publications, 2020)
Psoriasis is a chronic immune-mediated inflammatory disease that affects about 2%-4% of the population. Clinically typical erythemato-squamous papules and plaques of different sizes and shapes on the skin are characterized by the parallel appearance of epidermal hyperproliferation, inflammation and angioneogenesis. Although many factors are blamed in the etiology of psoriasis, genetic and environmental factors play a role in the pathogenesis of the disease. However, there may be fluctuations in psoriasis activity by hormonal changes and pregnancy. Overall, three out of every four psoriasis patients experience a change in the course of the disease during pregnancy. The proportion of those with improvement in the course of psoriasis is about twice as high as those with worsening. However, generalized pustular psoriasis of pregnancy seen in the last trimester of pregnancy can lead to serious maternal and neonatal morbidities and even mortality. On the other hand, some complications such as low birth weight, preterm birth, gestational diabetes, gestational hypertension, preeclampsia and emergency cesarean section have been reported more frequently in pregnant patients with severe psoriasis. Therefore, considering the adverse maternal and fetal outcomes of severe psoriasis and the fetal side effects of systemic psoriasis treatments, psoriasis in pregnant cases should be managed well by keeping the risk-benefit ratio in balance. In this article, the concerns and misconceptions of the patients with psoriasis about pregnancy and psoriasis interaction, pre-pregnancy counseling, the course of psoriasis during pregnancy, the pregnancy course in patients with psoriasis, and the management of psoriasis in pregnant women have been extensively reviewed, respectively.